Age Dependent Switching Role of Cyclin D1 in Breast Cancer - Carmela Rinaldi; Natalia Maria Malara; Rosalia D’Angelo; Antonina Sidoti; Attilio Leotta; Santo Lio; Basilio Caparello; Alessia Ruggeri; Vincenzo Mollace; Aldo Amato (Analytical Cellular Pathology)
Background: Cyclin D1 gene (CCND1) plays pivotal roles in the development of several human cancers, including breast cancer, functioning as an oncogene. The aim of this study was to better understand the molecular dynamics of ductal carcinomas with regard to proliferation and the ageing process.